Problematyka konfliktu interesów w funkcjonowaniu rynku kapitałowego - Parkitna, Agnieszka; Górski, Arkadiusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The study refers to the occurrence of conflicts of interest on the capital market, which negatively affects the functioning of the capital market, limits its development potential, and may even affect the outflow of investors, particularly those providing liquidity in the market. Today, the social responsibility of business entities becomes something important. It is a specific determinant of the company’s image and the basis of its operation. Word = Institution “brokerage house” should be associated with competence, honesty, or righteousness resulting from observance of the law and ethics principles of conducted business. The existence of a set of regulations (the Code of Good Practice for Brokerage Houses, the Act on Counteracting Unfair Market Practices) relating to the functioning of brokerage houses, there are situations in business practice that are not used to develop a capital market, based on a conflict of interest. Brokerage firms are obliged, on the one hand, to: sell shares and, on the other hand, recommend buying them. “Manipulation on the market” would mean entering into transactions that give false, misleading signals about supply, demand, and prices of equity instruments. To avoid conflicts of interest, there are special procedures in brokerage offices that prevent co-operation between competing departments: chinese walls. Each office additionally has rules governing the flow and control of confidential information. Such information may not be available, for example, between primary and secondary market forces, between sales departments and analysis departments. The indicated issues were brought together, focusing on the possible consequences of conflicts of interest. It emphasizes the difficulty of bringing justice through the necessity of showing the causal link between the conflict of interest and the possible loss of the investor. Then solutions were identified to protect against the negative aspects of the conflict of interest, and the proposals were presented in their conclusions
Keywords: konflikt interesów; rynek kapitałowy; ryzyko inwestycji giełdowych